Analysis of the Influence of Price and Product on Purchasing Decisions Mediated by Brand Image at Maybank Indonesia Finance Lampung Branch - Oktariansyah; Haryono, Budi; Wahyoedi, Soegeng (PT. Anagata Sembagi Education, 2024)
Maybank Indonesia Finance is a financing company operating in Indonesia. In this research, there are various factors that can underlie consumer purchasing decisions. Researchers will focus on price, product and brand image as factors that can encourage consumer purchasing decisions. The existence of these various factors made researchers interested in conducting research entitled